2011
DOI: 10.1152/ajpcell.00521.2010
|View full text |Cite
|
Sign up to set email alerts
|

In dialyzed squid axons oxidative stress inhibits the Na+/Ca2+ exchanger by impairing the Cai2+-regulatory site

Abstract: The Na+/Ca2+ exchanger, a major mechanism by which cells extrude calcium, is involved in several physiological and physiopathological interactions. In this work we have used the dialyzed squid giant axon to study the effects of two oxidants, SIN-1-buffered peroxynitrite and hydrogen peroxide (H2O2), on the Na+/Ca2+ exchanger in the absence and presence of MgATP upregulation. The results show that oxidative stress induced by peroxynitrite and hydrogen peroxide inhibits the Na+/Ca2+ exchanger by impairing the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Many studies reveal that ROS inactivates NCX, leading to a rise in cytoplasmic Ca 2+ and subsequent cell dysfunction [57]. For instance, in dialyzed squid axons, oxidative stress inhibits NCX by impairing the intracellular Ca 2+ -regulatory site [58]. In cardiac myocytes exposed to ischemia/reperfusion, which produces a burst of oxygen radicals, the NCX can operate in the reverse mode causing Ca 2+ influx into the cytoplasm [59].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reveal that ROS inactivates NCX, leading to a rise in cytoplasmic Ca 2+ and subsequent cell dysfunction [57]. For instance, in dialyzed squid axons, oxidative stress inhibits NCX by impairing the intracellular Ca 2+ -regulatory site [58]. In cardiac myocytes exposed to ischemia/reperfusion, which produces a burst of oxygen radicals, the NCX can operate in the reverse mode causing Ca 2+ influx into the cytoplasm [59].…”
Section: Discussionmentioning
confidence: 99%
“…ROS also gives rise to myocardial dysfunction in IR and are reported to alter NCX1 activity. DiPolo et al [35] have already demonstrated that oxidative stress inhibits the NCX by impairing the Cai 2+ -regulatory site in dialyzed squid axons. Soliman et al [36] used the patch-clamp technique to study the effects of the ROS, H 2 O 2 , on recombinant NCX1 splice variants.…”
Section: Conditions Related To Ncx During Irmentioning
confidence: 99%